Fun & learn 3R: a playbook for pre-school kids / Wei-Loon Koe ... [et al.] - Koe, Wei-Loon; Mohd Nordin, Noorain; Mohamed, Munirah; Awang, Amizatul Hawariah; Mohd Rafien, Nor Shahrina (2020)
Fun & Learn 3R is an educational playbook focusing on 3R concepts. It is designed for pre-school kids. Pre-school kids in Malaysia are lacking of environmental exposure because environmental education is provided to primary and secondary level students. Furthermore, there is a lack of suitable activities for pre-school kids to expose to environmental education. Therefore, this playbook is created as an edutainment learning tool for pre-school kids to obtain some early exposure of environmental knowledge. The main objective of this game is to develop visual perceptual skills and environmental interest among pre-school kids through a fun learning approach. In terms of its novelty, it comes with various hands-on and interactive activities to develop kid's environmental knowledge. Besides, it can also enhance the kid's psychomotor and visual perceptual skills which are important in their early learning stage. The benefits of this product are: i) it is easy to play ii) it builds early awareness iii) it helps to train environmental lovers who are able to save our natural resources and wildlife iv) reduce pollution. It is suitable to be used as a teaching aid by pre-school teachers or parents. Fun & Learn 3R is a superlative edutainment learning tool in 21st century.